SUPERVISI AKADEMIK PENGAWAS UNTUK MENINGKATKAN KOMPETENSI KEPALA DI TAMAN KANAK-KANAK LEGOKJAWA PANGANDARAN - Ratnawulan, Teti; Hanafiah; Yulia, Mira Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe and analyze the academic supervision process carried out by supervisors in improving the competencies of kindergarten principals at Legokjawa Pangandaran. The focus of this research includes four main aspects: planning, implementation, evaluation, and follow-up of academic supervision by the supervisors. The approach used in this study is a qualitative approach with a case study method. Data were collected through in-depth interviews, participatory observation, and documentation of academic supervision activities conducted at the school. The results of the study show that academic supervision was conducted systematically and collaboratively. Supervision planning was developed based on needs analysis and carried out together with the principals, taking into account the school context and previous evaluation results. Supervision implementation was conducted intensively and oriented toward professional development rather than mere assessment, using dialogical and reflective approaches. Supervision evaluation was carried out comprehensively and served as a means for principals to engage in self-assessment and improve their performance. Follow-up actions were conducted continuously through guidance, monitoring, and reinforcement of the principals’ programs, thus directly contributing to enhancing principals’ competencies in instructional and managerial leadership. The study concludes that academic supervision carried out in a planned, participatory, and continuous manner can serve as a strategic instrument to improve the professional capacity of principals, particularly in the context of early childhood education institutions. Keywords: academic supervision, school supervisor, principal, early childhood education (ECE).